Pre-hospital transfusion of plasma in hemorrhaging trauma patients independently improves hemostatic competence and acidosis. Issue 1 (December 2016) - Henriksen, Hanne; Rahbar, Elaheh; Baer, Lisa; Holcomb, John; Cotton, Bryan; Steinmetz, Jacob; Ostrowski, Sisse; Stensballe, Jakob; Johansson, Pär; Wade, Charles
Abstract Background The early use of blood products has been associated with improved patient outcomes following severe hemorrhage or traumatic injury. We aimed to investigate the influence of pre-hospital blood products (i.e. plasma and/or RBCs) on admission hemostatic properties and patient outcomes. We hypothesized that pre-hospital plasma would improve hemostatic function as evaluated by rapid thrombelastography (rTEG). Methods We conducted a prospective observational study recruiting 257 trauma patients admitted to a Level I trauma center having received either blood products pre-hospital or in-hospital within 6 hours of admission. Clinical data on patient demographics, blood biochemistry, injury severity score and mortality were collected. Admission rTEG was conducted to characterize the coagulation profile and hemostatic function. Results 75 patients received pre-hospital plasma and/or RBCs (PH group; nearly half received both RBCs and plasma) whereas 182 patients only received in-hospital blood products (RBCs, Plasma and Platelets) within 6 hours of admission (IH group). PH patients had lower Glasgow coma scale (GCS) scores, more penetrating injuries, lower systolic blood pressures, lower hemoglobin levels, lower platelet counts and greater acidosis upon ED admission than the IH group (allp < 0.05). Despite differences in type of injury and admission vitals indicating that the PH group had more signs of bleeding than the IH group, there were no significant differences in in-hospital mortality (PH 26.7% vs. IH 20.9% p = 0.31). When comparing rTEG variables between PH patients transfused with 0, 1 or 2 units of plasma, more pre-hospital plasma transfusion was tendency towards improved rTEG variables. When adjusting for pre-hospital RBC, pre-hospital plasma was associated with significantly higher rTEG MA (p = 0.012) at hospital admission. Discussion After adjusting for pre-hospital RBCs, pre-hospital plasma transfusion was independently associated with increased rTEG MA, as well as arrival indices of shock and hemodynamic instability. Besides more severe injury and worse clinical presentation, the group that received pre-hospital transfusion had early and late mortality similar to patients not transfused pre-hospital. Conclusions These data suggest that early administration of plasma can provide significant hemostatic and potential survival benefit to severely hemorrhaging trauma patients.